Scoping Review: Dampak COVID-19 pada Wanita Hamil - Reza Rizqita Maulana Hidayat; Ratna Dewi Indiastuti; Oky Haribudiman (UNISBA Press, 2022)
Abstract. Corona Virus Disease 2019 (COVID-19) is a disease that arises due to infection with Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-COV-2) which was identified at the end of December 2019 and has become a worldwide pandemic. Covid-19 has infected the entire world population, including pregnant women. The susceptibility of pregnant women to infection is the background for the need for studies on the impact of Covid-19 on pregnant women. The purpose of this study was to determine the impact of Covid-19 on pregnant women. This research is a Scoping Review. Databases used are Science Direct, Emerald, SpringerLink. Articles that match the inclusion criteria from full text journals, in English and Indonesian, prospective and retrospective cohorts, and journals for 2019-2021 are 2,462 articles. Articles included in the exclusion criteria were 18 articles. The results of the feasibility test based on PICOS were 18 articles. After a critical study, the remaining articles were 10 articles. The results of the analysis of 10 articles, 5 articles stated that the most common impact on pregnant women with Covid-19 was an increase in cases of preeclampsia, preterm birth and births using the C-section method. Three articles state that another outcome that appears on pregnant women with Covid-19 is death. Two other articles stated that Covid-19 infection had no impact on pregnant women with Covid-19. The conclusion of this study is that the most common outcome that occurs in pregnant women with Covid-19 is an increase in births by C-section method, preterm and preeclampsia, and death. Abstrak. Corona Virus Disease 2019 (COVID-19) penyakit yang timbul akibat infeksi Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-COV-2) yang teridentifikasi pada akhir bulan Desember 2019 dan telah menjadi pandemi di seluruh dunia. Covid-19 telah menjangkit seluruh penduduk dunia tidak terkecuali wanita hamil. Kerentanan wanita hamil terhadap infeksi menjadi latar belakang perlunya studi tentang dampak Covid-19 pada wanita hamil. Tujuan penelitian ini adalah untuk mengetahui dampak Covid-19 pada wanita hamil. Penelitian ini merupakan Scoping Review. Database yang digunakan Science Direct, Emerald, SpringerLink. Artikel yang sesuai dengan kriteria inklusi dari jurnal full text, berbahasa Inggris dan berbahasa Indonesia, cohort prospektif dan retrospektif, dan jurnal tahun 2019-2021 sebanyak 2.462 artikel. Artikel termasuk dalam kriteria eksklusi sebanyak 18 artikel. Hasil uji kelayakan berdasarkan PICOS sebanyak 18 artikel. Setelah dilakukan telaah kritis, tersisa sebanyak 10 artikel yang akan digunakan pada penelitian ini. Hasil analisis 10 artikel, 5 artikel menyatakan dampak tersering pada wanita hamil dengan Covid-19 adalah peningkatan kasus preeclampsia, preterm birth dan kelahiran dengan metode C-section. Tiga artikel menyatakan dampak lain yang muncul pada wanita hamil dengan Covid-19 adalah kematian. Dua artikel lain menyatakan infeksi Covid-19 tidak menimbulkan dampak pada wanita hamil dengan Covid-19. Kesimpulan dari penelitian ini adalah dampak tersering yang terjadi pada wanita hamil dengan Covid-19 adalah peningkatan kelahiran dengan metode C-section, preterm dan preeclampsia, dan kematian.